ARCHAEOLOGICAL MONUMENTS OF EARLY MEDIEVAL USTYURT (V-XI CENTURIES) (TAMADDUN NURI JURNALI, 2024)
There are sources from the early Middle Ages about the Ustyurt region bordering the Khorezm oasis. Among them are Ibn Ruste, Al Istakhri (IX-X), Ibn Fadlan (922), Al Muqaddasi (985), Ibn Battuta (1333), A. Jenkinson (1558) and scientists of the new era, which we learned about in his works.